Kvantni Zenov pojav - Smolkovič, Aleks (Matrika, 2016)
In order for an arrow to move, it has to change its position in every moment of its flight. If we take a look at it at a certain moment, it appears stationary. The arrow is not moving in any fixed moment, therefore it is not moving at all. This is Zeno's famous arrow paradox. This work is going to take a look at an analogous phenomenon in quantum mechanics. It is going to illustrate it with a simple problem, discuss an experimental confirmation of the theoretical results and in the end mention its practical application with quantum Zeno dynamics.
Keywords: kvantna mehanika; kvantna Zenova dinamika; quantum mechanics; quantum Zeno dynamics; Zeno effect; Zenov pojav